Comparison of taxonomic diversity of microorganisms isolated from oil reservoir waters of Western Kazakhstan deposits with foreign oil fields - Tolegen, N.E.; Ondasynova, D.G.; Bakhytuly, K.; Ibatova А.А. (Fundamental and Experimental Biology, 2022)
The article describes a variety of microorganisms, isolated from oil reservoir waters of different oilfields that are main objects in studying the micrоbiаl еnhаnсеd оil rесоvеrу (МЕОR) methods. Microorganisms can generate a number of potentially useful metabolites (biomass, biosurfactants, bioacid, biosolvents, biopolymer, biogas) for oil recovery. These metabolites help to reduce the oil’s viscosity and the interfacial friction between oil and water as a surfactant, increase its porosity and permeability. The article discusses the taxo-nomic biodiversity of microorganisms of oil-formation waters of three active wells of the “Zhetybai”, “Kulsary”, and “Akingen” fields and from different oil deposits across the world for several years. The significance of oil microorganisms, their research, the importance of MEOR processes, comparison of oil microbes between international and Western Kazakhstan oil reserves and future of these microorganisms are widely studied. The article provides information on microorganisms, such as Bacillus sp., Pseudomonas sp., that are more immune to adverse shifts in environmental changes. These genera produce surfactants, gases, alcohols, acids, and biopolymers. The similarity of the taxonomic biodiversity of oil microorganisms of oilfields in Western Kazakhstan and their prospects, as well as the use of microorganisms from the distant countries’ oil-fields in the MEOR processes are analyzed.